2023
DOI: 10.1002/ptr.7830
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on the anxiolytic and hypnotic effects of flower extracts in in vivo pre‐clinical studies published from 2010 to 2020

Abstract: Anxiety disorders are prevalent conditions in the world population, whose standard approaches include pharmacotherapy, psychotherapy, and combinations of these interventions. Different classes of psychopharmaceuticals are recommended as the first line of drugs to treat these disorders, which can have several adverse effects, treatment resistance, dependence, and drug–drug interactions making it necessary to search for new therapeutic agents. In particular, diazepam (DZP), a prototype drug from the group of ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Therefore, we selected the highest dose for each component at 50, 25, and 10 mg/kg oral doses for this current study. When testing hypnotic, sedative, anxiolytic, and other effects on mice and rats, DZP (1 to 3 mg/kg) is frequently used as a standard drug [ 97 , 98 , 99 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we selected the highest dose for each component at 50, 25, and 10 mg/kg oral doses for this current study. When testing hypnotic, sedative, anxiolytic, and other effects on mice and rats, DZP (1 to 3 mg/kg) is frequently used as a standard drug [ 97 , 98 , 99 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several investigations have found that QR (50 and 100 mg/kg) has a strong antidepressant effect in a mouse model (Anjaneyulu et al, 2003;. In addition, DZP (1-3 mg/kg) is often used as a standard treatment for studying sedative, hypnotic, anxiolytic, and other effects on rats and mice Iwashita et al, 2023;Meneses et al, 2023). TS is a barbiturate that is commonly used intravenously to induce general anesthesia fast.…”
Section: Selection Of Test Doses For Scl Qr Dzp and Tsmentioning
confidence: 99%